Rural Livelihood Diversification and Economic Adaptation in East Kalimantan: Evidence from Six Village Communities - Sayaza, Mas Davino; Stephanie, Endah Nadiyas (Jurnal Rekayasa Lingkungan dan Biosistem, 2025)
This study examines rural livelihood diversification patterns across six village communities in East Kalimantan Province, Indonesia. Using qualitative methodology including focus group discussions, in-depth interviews, and seasonal calendar development, the research analyzes how rural households adapt their economic strategies within contexts shaped by palm oil expansion and extractive industries. The study was conducted in Tepian Indah, Tepian Langsat, Tepian Makmur, Tebangan Lembak, Tepian Baru, and Tepian Budaya villages within Bengalon Subdistrict, Kutai Timur Regency. Findings reveal that livelihood strategies operate within complex intersections of demographic composition, land allocation systems, infrastructure access, and institutional capacity. Oil palm cultivation dominates five villages through both independent farming and plasma partnership arrangements, while mining employment characterizes Tebangan Lembak. Infrastructure disparities create differential opportunities for economic activities, with variations in electrical access, transportation connectivity, and water security affecting household adaptation strategies. Gender analysis shows women's critical roles in autonomous economic activities and environmental adaptation, though often underrecognized in development planning. Weak institutional capacity limits collective action for market integration despite formal farmer group existence. The study contributes to understanding rural economic adaptation in resource-rich regions by demonstrating how livelihood diversification reflects responses to both opportunities and constraints created by extractive industry presence.